Local Ownership, Inclusivity and Civil-Military Synergy in EU External Action: The Case of EU Support to Security Sector Reforms in Mali - Vogelaar, Gabriëlla (Journal of Regional Security, 2018)
The evolution of the European Union (EU) as a security and peacebuilding actor rais- es questions as to its identity as a largely civilian power alongside the development of its military capabilities. Specifically, a key challenge lies in how its civilian and military capabilities relate to each other as they develop, with increasing expectations from the EU to act effectively across its peacebuilding and conflict prevention interventions. The EU aims to do more to link top-down and bottom-up approaches, but there is currently a lack of focus on the latter. In exploring the challenges and opportunities for the EU to enhance its potential for civil-military synergies in crisis management, the paper takes a holistic whole-of-society perspective, asking questions about the level of inclusivity and local ownership in its approaches. The paper takes a closer look at the European Union Training Mission (EUTM) and European Union Capacity Building Mission in Mali (EUCAP Sahel Mali) as a specific case. Based on the findings, this paper argues the EU could be more effective, especially at the operational level, by taking a more bottom-up approach in the areas of designing, planning, monitoring and evaluating interventions. The EU will need to find ways to better embed its interventions in local realities, for instance by working with local civil society in the EU’s security sector reform efforts, and offering platforms for more civilian oversight and feedback mechanisms. Only then, with a stronger focus on the inclusivity and local ownership aspects of civil and military action of the EU, will it be able to better address the ‘intangible aspects’ of security sector reform.